2014
DOI: 10.15678/znuek.2014.0933.0907
|View full text |Cite
|
Sign up to set email alerts
|

The Constraints and Problems in Team Performance Management

Abstract: A wide range of factors can affect team performance: setting clear and achievable goals, allocating individual work, utilizing an individual's skills, monitoring performance, maintaining team cohesion and identity, being able to handle internal conflicts, maintaining relationships with other teams, systems and resources available to teams and the quality of leadership. These problems and constraints affecting team performance management (TPM) are found on a global scale irrespective of a country's individual w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Actually, the authors of the IMO models showed that, in the case of P-processes, "many of the mediational factors that intervene and transmit the influence of inputs to outcomes are not processes, but emergent cognitive or affective states", that the "I-P-O framework limits research by implying a single-cycle linear path from inputs through outcomes", and that the I-P-O framework "tends to suggest a linear progression of main effect influences proceeding from one category to the next" [23] (p. 520), without considering emergent states that develop during team existence and have an impact on team outcomes. The IMO model is currently widely accepted in the team management literature [24]. The improved framework for understanding teamwork is presented in Figure 2.…”
Section: Understanding Teamwork Effectivenessmentioning
confidence: 99%
See 4 more Smart Citations
“…Actually, the authors of the IMO models showed that, in the case of P-processes, "many of the mediational factors that intervene and transmit the influence of inputs to outcomes are not processes, but emergent cognitive or affective states", that the "I-P-O framework limits research by implying a single-cycle linear path from inputs through outcomes", and that the I-P-O framework "tends to suggest a linear progression of main effect influences proceeding from one category to the next" [23] (p. 520), without considering emergent states that develop during team existence and have an impact on team outcomes. The IMO model is currently widely accepted in the team management literature [24]. The improved framework for understanding teamwork is presented in Figure 2.…”
Section: Understanding Teamwork Effectivenessmentioning
confidence: 99%
“…In the case of the input area, the organizational/contextual level may consist of the HR system, organizational climate and organizational culture. This level of input For understanding many of the potential constructs and variables that can be included in the IMOI models, author Urlych [24] presented a framework for assessing teamwork effectiveness, presented in Figure 3. From Figure 3, it is obvious that many different relations need to be included in exploring teamwork effectiveness.…”
Section: Understanding Teamwork Effectivenessmentioning
confidence: 99%
See 3 more Smart Citations